2001
DOI: 10.1007/s11883-001-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent findings in the study of postprandial lipemia

Abstract: The study of postprandial metabolism is in the early stages compared with other areas of atherosclerosis research. Recent advances in postprandial research have included improvements in methodology and the investigation of factors that modulate the lipemic response to a meal. Enough studies have now been performed that normal ranges have been identified for blood triacylglycerol (TAG) concentrations that occur after a healthy patient consumes a standardized-mixed meal or a high-fat shake designed to elicit lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 44 publications
0
41
0
2
Order By: Relevance
“…In Type 2 diabetes postprandial hyperglycaemia is an independent risk factor for cardiovascular disease [2] and a stronger predictor of cardiovascular mortality than fasting plasma glucose [3]. There is mounting evidence to suggest that delayed postprandial lipaemia represents an independent cardiovascular risk factor [4]. Endothelial dysfunction precedes [5] and predicts [6] overt cardiovascular disease and is therefore a potential mechanism linking the postprandial state to cardiovascular risk [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Type 2 diabetes postprandial hyperglycaemia is an independent risk factor for cardiovascular disease [2] and a stronger predictor of cardiovascular mortality than fasting plasma glucose [3]. There is mounting evidence to suggest that delayed postprandial lipaemia represents an independent cardiovascular risk factor [4]. Endothelial dysfunction precedes [5] and predicts [6] overt cardiovascular disease and is therefore a potential mechanism linking the postprandial state to cardiovascular risk [7].…”
Section: Introductionmentioning
confidence: 99%
“…The most adequate way to experimentally reproduce the postprandial lipemia condition appears to be the administration of a standardized OFL to fasting patients. 28 This model has been widely applied in relatively small sample of subjects to study the postprandial lipemia effect on inflammatory parameters, 29,30 circulating markers of endothelial dysfunction 31,32 and prothrombotic variables. 33,34 So, we observed that 6-month treatment is associated to a significant improvement of basal level of sICAM-1 (À17.3%), IL-6 (À31.6%) and Hs-CRP (À33.3%) in nondiabetics, whereas in BG (À3.7%), Tg (À11.2%), sICAM-1 (À16.5%), IL-6 (À36.6%) and Hs-CRP (À25.0%) in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…modulate particle size and/or composition) so that they become less atherogenic. In general, any factor that reduces postprandial lipidaemia may be considered to be cardio-protective (Parks, 2001;Petitt & Cureton, 2003).…”
Section: Alcohol and Postprandial Metabolismmentioning
confidence: 99%